A disputa pelo poder simbólico no escândalo do mensalão - Silva, José Henrique P. e (2011)
The work has a objective emphasize important moments in the dispute for symbolic power of the political crisis occurred in mensalão sacandal. The dispute will be show from the discursivity of the newspaper Folha de S.Paulo (editorial) and the Presidency (speeches and interviews) elaborated over the plots and subplots that required the construction and mobilization of the senses in an attempt to contest or sustain a determined view about the social world, leaving political consequences to beinvestigated